SPATIAL ANALYSIS OF DENGUE HEMORRHAGIC FEVER IN EAST MANGGARAI, INDONESIA: A CASE STUDY - Siga, Wilibaldus Julian; Astutik, Erni; Ximenes, Yohanes (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2023)
Background: East Manggarai is one of the District in East Nusa Tenggara Province with a high transmission area and a high number of Dengue Hemorrhagic Fever cases. Spatial analysis can provide spatial information related to the distribution pattern of DHF. Purpose: To spatially analyze the cases of DHF in East Manggarai District in 2021. Methods: This study used a descriptive survey method with a case study design sampling technique, Purposive sampling approach used a sample size of 103 cases. Data processing and spatial data analysis use Quantum Geographic Information Systems software with Nearest Neighbor Analysis and buffer analysis to describe the distribution of cases based on population density, House Index, Container Index, and Buffer Zone. Results: Spatial analysis using QGIS showed that the Nearest Neighbor Index was 0.323 < 1, and the CI value was 34.7, the HI value was 54 while the buffer zone showed the tendency for dengue transmission to occur in most cases within a radius of 100 meters. Conclusion: The pattern of DHF transmission is clustered, the sub-districts of Borong, Rana Mese, and Komba became the sources of DHF transmission where Container Index and House Index were classified as high categories, and population density was classified as high and low categories. Preventive action such as eliminating mosquito breeding areas were essential.